Gene Expression of NLRP3 Inflammasome in Celiac Disease of Iraqi Children - Anwar I. S. Al-Assaf; Hiba M. Ali; Ali H. Ad'hiah (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2021)
Celiac disease (CD) is an autoimmune disorder characterized by chronic inflammation that essentially affects the small intestine and is caused by eating gluten-containing foods. This study sought to determine gene expression of NLRP3 Inflammasome in peripheral blood of Iraqi CD children using quantitative real-time PCR (qRT-PCR) assay. Thirty children with CD (12 males and 18 females) were enrolled in the study and their age range was 3-15 years. The diagnosis of the disease was confirmed by serological examinations and intestinal endoscopy. A control sample of 20 age-matched healthy children was also included. The children were stratified for age, gender, body max index (BMI), histological findings, and marsh classification. Further, the sera were examined for IgA anti-tissue transglutaminase (tTG) antibody, IgA anti-gliadin antibody, and interleukin-1 beta (IL-1Î²). Based on Marsh classification, the results revealed that the majority of patients (70%) had partial villous atrophy (Marsh Ð¨ 3A), while children with subtotal and total villous atrophy (Marsh III: 3B/3C) were presented with a lower frequency (30.0%). Neither Marsh I nor Marsh II has been observed among the patients studied. Serum levels of anti-tTG and anti-gliadin IgA antibodies were significantly higher in CD children than in control children (73.8 and 31.8 vs. 0.8 U//ml, respectively; p < 0.001). Conversely, IL-1Î² serum level was decreased in CD children but the difference was not significant (35.5vs. 53.4 pg/ml; p = 0.285). In the case of NLRP3 inflammasome, the Relative Fold Change method (2-âˆ†âˆ†Ct) was used to assess the gene expression. The results revealed that the expression of NLRP3 inflammasome was decreased by 0.594 fold in CD children. In conclusion, the NLRP3 inflammasome was down-regulated in the present sample of CD children, and it was accompanied by a decreased serum level of IL-1Î².